2009
DOI: 10.1111/j.1743-6109.2008.01058.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Changes in Sexual Desire, Satisfying Sexual Activity and Personal Distress as Measured by the Profile of Female Sexual Function, Sexual Activity Log, and Personal Distress Scale in Postmenopausal Women with Hypoactive Sexual Desire Disorder

Abstract: Introduction Transdermal testosterone patch (TTP) treatment produced statistically significant improvements in a satisfying sexual activity (SSA), sexual desire, and personal distress in postmenopausal women suffering from hypoactive sexual desire disorder (HSDD), but clinical significance of these changes was not determined. Aim To quantify the magnitude of change in three principal outcomes measures determined by HSDD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 23 publications
(27 reference statements)
0
17
0
1
Order By: Relevance
“…Another common variation is to consider the percentage change score in the instrument under consideration [33], rather than the absolute score change. Determination of what constituted an important difference was sometimes based upon the use of methodology more typically used to assess diagnostic accuracy, such as receiver operating characteristic curves [6],[11],[20], or more complex statistical approaches. It is worth noting that the anchor method was not always successful in deriving values for an important difference; failure was usually due to either practical or methodological difficulties [17],[23].…”
Section: Resultsmentioning
confidence: 99%
“…Another common variation is to consider the percentage change score in the instrument under consideration [33], rather than the absolute score change. Determination of what constituted an important difference was sometimes based upon the use of methodology more typically used to assess diagnostic accuracy, such as receiver operating characteristic curves [6],[11],[20], or more complex statistical approaches. It is worth noting that the anchor method was not always successful in deriving values for an important difference; failure was usually due to either practical or methodological difficulties [17],[23].…”
Section: Resultsmentioning
confidence: 99%
“…The question [31] always arises: are these results clinically significant? The DISF has been normalized to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…1 Female sexual dysfunction can include a decrease in sexual desire and arousal, altered or absent orgasm, and dyspareunia. Recent findings from the Australian Longitudinal Study of Health and Relationships found that two thirds of Australian women experienced one or more sexual difficulties, of which at the 12 month follow-up persisted in nearly three quarters of the women and with one third reporting a new difficulty.…”
Section: Introductionmentioning
confidence: 99%